THE ASPECTS OF ANOMALY IN SEMANTIC STUDY (An effort to increase students competence in semantic study) - Kani Sullam Taufik (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2014)
Study of meaning in fiction stories plays an important role in the use of language as a means of communication. This writing attempts to describe the aspects of anomaly from which the meaning of words, phrases, and sentences can be semantically orgrammatically analyzed. In order to make a distinction between semantic anomaly and grammatical anomaly, the most commonly encountered criterion for separating each of them is corrigibility.Thus, corrigibility is the main factor to identify the aspects of anomaly utilized in the texts of the stories. The anomaly made by the writer offiction stories includes Pleonasm, Zeugma,Dissonance and Improbability .